The CF-CIRC study: a French collaborative study to assess the accuracy of Cystic Fibrosis diagnosis in neonatal screening - Bellon Gabriel; Reix Philippe; Huet Frédéric; Deneuville Eric; Bui Stéphanie; Roussel Delphine; Sermet-Gaudelus Isabelle; Lenoir Gérard; Edelman Aleksander (BMC, 2006)
Abstract Background Cystic fibrosis (CF) is caused by mutations in the gene encoding for the CF transmembrane conductance regulator (CFTR) protein, which acts as a chloride channel after activation by cyclic AMP (cAMP). Newborn screening programs for CF usually consist of an immunoreactive trypsinogen (IRT) assay, followed when IRT is elevated by testing for a panel of CF-causing mutations. Some children, however, may have persistent hypertrypsinogenemia, only one or no identified CFTR gene mutation, and sweat chloride concentrations close to normal values. In vivo demonstration of abnormal CFTR protein function would be an important diagnostic aid in this situation. Measurements of transepithelial nasal potential differences (NPD) in adults accurately characterize CFTR-related ion transport. The aim of the present study is to establish reference values for NPD measurements for healthy children and those with CF aged 3 months to 3 years, the age range of most difficult-to-diagnose patients with suspected CF. The ultimate goal of our study is to validate NPD testing as a diagnostic tool for children with borderline results in neonatal screening. Methods/Design We adapted the standard NPD protocol for young children, designed a special catheter for them, used a slower perfusion rate, and shortened the protocol to include only measurement of basal PD, transepithelial sodium (Na+) transport in response to the Na+ channel inhibitor amiloride, and CFTR-mediated chloride (Cl-) secretion in response to isoproterenol, a β-agonist in a Cl- free solution. The study will include 20 children with CF and 20 healthy control children. CF children will be included only if they carry 2 CF-causing mutations in the CFTR gene or have sweat chloride concentrations > 60 mEq/L or both. The healthy children will be recruited among the siblings of the CF patients, after verification that they do not carry the familial mutation. Discussion A preliminary study of 3 adult control subjects and 4 children older than 12 years with CF verified that the new protocol was well tolerated and produced NPD measurements that did not differ significantly from those obtained with the standard protocol. This preliminary study will provide a basis for interpreting NPD measurements in patients with suspected CF after neonatal screening. Earlier definitive diagnosis should alleviate parental distress and allow earlier therapeutic intervention and genetic counseling.